Composite material, preparation thereof and use thereof in organic solar cells
By using composite materials of polyoxylate (POM) clusters and carbazole-based self-assembled monolayers (SAM) in organic solar cells, the stability and efficiency of the hole transport layer are solved, and efficient organic solar cell performance is achieved.
Patent Information
- Application Number
- CN202411914648.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-12
- Filing Date
- 2024-12-24
- Publication Date
- 2025-08-12
AI Technical Summary
The hole transport layer materials of existing organic solar cells have shortcomings in terms of stability and efficiency, such as phase separation of PEDOT:PSS, harsh processing conditions of MoO3, low conductivity of NiO and deep energy level problems of POM.
A composite material of polymetallic acid (POM) clusters and carbazole-based self-assembled single layer (SAM) are used to form a discontinuous layer on the substrate by sequential deposition. The POM clusters act as void filler and top surface passivator to form a tightly inserted composite material.
The efficiency and long-term stability of organic solar cells are improved, especially the sufficient coverage of HTL is achieved under thin film conditions, reducing processing complexity.
Smart Images

Figure CN120475846A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite material, for example, in particular but not exclusively, a composite material having a self-assembled monolayer (SAM) of polyoxometalate (POM) clusters and a carbazole-based compound for use in organic solar cells (OSCs). The present invention also relates to the preparation of the composite material and the use of the composite material in OSCs. Background Art
[0002] The hole transport layer (HTL) is believed to play a key role in determining the efficiency and stability of pin-structured organic photovoltaics (OPVs) / organic solar cells (OSCs). Typically, HTLs can include materials such as polyelectrolytes, metal oxides, p-type self-assembled monolayers (SAMs), and polyoxometalates (POMs). However, these materials can exhibit various drawbacks in OPV / OSC applications.
[0003] In particular, polyelectrolyte HTLs such as PEDOT:PSS may suffer from phase separation leading to instability. In addition, their relatively low optical band gap may induce some parasitic absorption, thereby impairing light collection in the active layer. Metal oxides such as MoO3, WO3, NiO, etc. generally require harsh processing conditions. P-type SAMs may face challenges in forming complete coverage on the bottom electrode. POMs may suffer from low conductivity and deep energy levels, which will hinder hole extraction from the bottom electrode when applied as a thick layer.
[0004] The present invention therefore seeks to obviate or at least mitigate such disadvantages by providing new or otherwise improved HTL materials for OPV / OSCs. Summary of the Invention
[0005] In a first aspect of the present invention, a composite material for an organic solar cell is provided, the composite material comprising a polyoxometalate (POM) cluster and a self-assembled monolayer (SAM) of a carbazole-based compound.
[0006] Optionally, the carbazole-based compound has the formula:
[0007]
[0008] wherein: R1 and R2 each represent mono- or di-substitution and are each independently selected from the group consisting of hydrogen, halogen, alkyl, alkoxy, fused ring, non-fused ring, and combinations thereof; n is a positive integer from 1 to 3; and A is an anchor group comprising an acid moiety.
[0009] Optionally, R1 and R2 are each independently selected from the group consisting of H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 alkoxy, C6-C10 aryl, C5-C10 heteroaryl, and combinations thereof.
[0010] Optionally, A is selected from the group consisting of carboxyl, sulfonyl, mercapto and phosphono.
[0011] Optionally, R1 and R2 are the same.
[0012] Optionally, R1 and R2 are different.
[0013] In optional embodiments, the carbazole-based compound has a formula selected from the group consisting of:
[0014]
[0015]
[0016] wherein: R1 and R2 each represent a monosubstitution and are selected from the group consisting of H, F, Cl, Br, I, methyl, ethyl, methoxy, ethoxy, tert-butoxy, and phenyl; n is 1-3; and A is selected from the group consisting of carboxyl, sulfo, mercapto, and phosphono.
[0017] In optional embodiments, the carbazole-based compound has a formula selected from the group consisting of:
[0018]
[0019]
[0020] wherein: R1 represents a monosubstitution and is selected from the group consisting of H, F, Cl, Br, I, methyl, ethyl, methoxy, ethoxy, tert-butoxy, and phenyl; n is 1-3; and A is selected from the group consisting of carboxyl, sulfo, mercapto, and phosphono.
[0021] Optionally, the carbazole-based compound has a formula selected from the group consisting of:
[0022]
[0023]
[0024] In optional embodiments, the POM cluster comprises a Keggin structure.
[0025] In optional embodiments, the POM cluster comprises a Dawson structure.
[0026] Optionally, the POM cluster has the formula X a YMn M' 12-n O 40 , and wherein X is a cation selected from the group consisting of: H + NH4 + NR4 + , wherein R is a C1-C4 linear or branched alkyl group; a is 3 or 4; Y is selected from the group consisting of Si and P; M and M' are selected from the group consisting of W and Mo; and n is 0-12.
[0027] Optionally, the POM cluster has the formula H3PW 12 O 40 .
[0028] Optionally, the POM cluster has the formula X b Y2M n’ M' 18-n’ O 62 , and wherein X is a cation selected from the group consisting of: H + NH4 + NR4 + , wherein R is a C1-C4 linear or branched alkyl group; b is 6 or 8; Y is selected from the group consisting of Si and P; M and M' are selected from the group consisting of W and Mo; and n' is 0-18.
[0029] In an optional embodiment, the POM clusters are configured to form a discontinuous layer on the SAM.
[0030] Optionally, the POM clusters are intercalated with the SAM by filling into the nanovoids of the SAM.
[0031] Optionally, the SAM and POM clusters have a concentration ratio of about 1:1 to about 1:40.
[0032] In an optional embodiment, the composite material is a hole transport layer material.
[0033] In a second aspect of the present invention, a method for preparing a composite material according to the first aspect is provided, the method comprising the steps of: a) depositing a SAM of a carbazole-based compound on a substrate to form a first substrate; and b) depositing POM clusters on the first substrate to form a discontinuous layer on the first substrate.
[0034] Optionally, step b) is performed without pre-rinsing the first substrate.
[0035] Optionally, step b) is performed without post-annealing.
[0036] Optionally, steps a) and b) are each performed by spin coating.
[0037] In a third aspect of the present invention, an organic solar cell is provided. The organic solar cell comprises a hole transport layer, wherein the hole transport layer comprises the composite material according to the first aspect.
[0038] In an optional embodiment, the organic solar cell further comprises: an anode and a cathode, a hole transport layer being disposed between the anode and the cathode; an electron transport layer being disposed between the anode and the cathode; and a photoactive layer being disposed between the hole transport layer and the electron transport layer.
[0039] Optionally, the photoactive layer is in direct contact with the hole transport layer and the electron transport layer.
[0040] Optionally, the photoactive layer is configured as any one of the following structures: bulk heterojunction, quasi-planar heterojunction, and pseudo-bilayer. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The present invention will now be described in more detail, by way of example only, with reference to the accompanying drawings, in which:
[0042] Figure 1A is a schematic diagram illustrating a Keggin structure of a polyoxometalate (POM) cluster according to an embodiment of the present invention;
[0043] Figure 1B is a schematic diagram illustrating the Dawson structure of a polyoxometalate (POM) cluster according to an embodiment of the present invention;
[0044] Figure 1C is a schematic diagram illustrating a cross-sectional view of an organic solar cell (OSC) according to an embodiment of the present invention;
[0045] Figure 1D shows the chemical structure of an electron donor used in a photoactive layer according to some embodiments of the present invention;
[0046] Figure 1E shows the chemical structure of an electron acceptor used in a photoactive layer according to some embodiments of the present invention;
[0047] Figure 2 is a schematic diagram illustrating the chemical structures of Br-PA and HPWO in the device and the pattern of the Br-PA:HPWO sequentially deposited composite (SDC);
[0048] Figure 3 shows the optical transmittance of ITO substrates coated with different HTLs
[0049] Figure 4 The dependence of the absorbance of Br-PA:HPWO SDC on the concentration of HPWO solution is shown;
[0050] Figure 5A The work function and HOMO energy level determined by UPS are shown;
[0051] Figure 5B The energy level alignment of HTL-modified ITO (work function) and PM6 (HOMO level) is shown;
[0052] Figure 6A AFM height image of fresh HTL film of single Br-PA is shown;
[0053] Figure 6B shows the AFM height image of a fresh HTL film of HPWO;
[0054] Figure 6C AFM height image of fresh HTL film of Br-PA:HPWO SDC is shown;
[0055] Figure 7A Energy dispersive X-ray spectroscopy (EDS) elemental mapping of Br for single Br-PA on ITO is shown;
[0056] Figure 7B shows the EDS elemental mapping of W of single Br-PA on ITO;
[0057] Figure 7C shows the EDS elemental mapping of Br of Br-PA:HPWO SDC-HTL on ITO;
[0058] Figure 7D shows the EDS elemental mapping of W of Br-PA:HPWO SDC-HTL on ITO;
[0059] Figure 7E Overlapping EDS elemental mapping of Br and W of Br-PA:HPWO SDC-HTL on ITO is shown;
[0060] Figure 8 is a table summarizing the P:In intensity ratios of ITO substrates coated with different HTLs;
[0061] Figure 9A In 3d images of an ITO substrate coated with Br-PA are shown. 3 / 2 XPS spectrum;
[0062] Figure 9B In 3d images of an ITO substrate coated with HPWO are shown. 3 / 2 XPS spectrum;
[0063] Figure 9CThe In 3d morphology of an ITO substrate coated with Br-PA:HPWO is shown. 3 / 2 XPS spectrum;
[0064] Figure 10A shows the XPS spectrum of the P 2p core level of the ITO substrate coated with a single Br-PA;
[0065] Figure 10B shows the XPS spectrum of the P 2p core level of the ITO substrate coated with a single HPWO;
[0066] Figure 10C The XPS spectrum of the P 2p core level of the ITO substrate coated with a single Br-PA:HPWO SDC is shown;
[0067] Figure 11 The ESR spectra of Br-PA, HPWO, PM6 and their blends as solid powders are shown, where g is the g-factor;
[0068] Figure 12A The contact angle of water on single Br-PA is shown;
[0069] Figure 12B The contact angle of water on HPWO is shown;
[0070] Figure 12C Shown is the contact angle of water on the Br-PA:HPWO composite;
[0071] Figure 13A The contact angle of diiodomethane on single Br-PA is shown;
[0072] Figure 13B The contact angle of diiodomethane on HPWO is shown;
[0073] Figure 13C The contact angle of diiodomethane on the Br-PA:HPWO bilayer is shown;
[0074] Figure 14 is a table summarizing the average contact angles and surface energies of different HTLs;
[0075] Figure 15A The XPS spectrum and fitting curve of W 4f of ITO / HPWO are shown;
[0076] Figure 15B The XPS spectrum and fitting curve of W 4f of ITO / PM6 / HPWO are shown;
[0077] Figure 15C is a table summarizing the fitting parameters of the XPS spectra of ITO / HPWO and ITO / PM6 / HPWO;
[0078] Figure 16 shows the chemical structure of the ETL material employed in the device according to an embodiment of the present invention;
[0079] Figure 17 The dependence of the PCE of the HPWO-based devices on the HPWO concentration is shown.
[0080] Figure 18A JV curves of OSCs based on single HPWO coated by methanol solutions with different concentrations are shown;
[0081] Figure 18B is a table summarizing the photovoltaic parameters of OSCs based on HPWO HTL coated by methanol solutions with different concentrations;
[0082] Figure 19A shows the JV curves of devices including different HTLs;
[0083] Figure 19B is a table summarizing the photovoltaic parameters of OSCs based on PM6:BTP-eC9:L8-F and different HTLs;
[0084] Figure 20A JV curves of OSCs based on single Br-PA without solvent washing or with methanol washing are shown;
[0085] Figure 20B is a table summarizing the photovoltaic parameters of Br-PA HTL-based OSCs without solvent rinsing treatment or with methanol rinsing;
[0086] Figure 21 EQE spectra of devices including different HTLs are shown;
[0087] Figure 22 shows the integrated short-circuit current density of OSC devices including different HTLs;
[0088] Figure 23A shows the JV curves of OSCs based on Br-PA:HPWO HTL, where HPWO was coated at different concentrations in methanol;
[0089] Figure 23B is a table summarizing the photovoltaic parameters of OSC devices using Br-PA:HPWO SDC as HTL, where HPWO was coated at different concentrations in methanol;
[0090] Figure 24A JV curves of OSCs using Br-PA:HPWO mixtures with different composition ratios as HTL are shown;
[0091] Figure 24Bis a table summarizing the photovoltaic parameters of OSC devices using Br-PA:HPWO mixtures as HTL, where HPWO is coated with different composition ratios;
[0092] Figure 25A The pore area of 1.008 cm based on different HTLs is shown. 2 JV curve of large-area OSC;
[0093] Figure 25B Shows the 1-cm 2 Performance progress of OSC;
[0094] Figure 25C This is a summary of representative large-area (~1cm 2 ) Table of photovoltaic parameters of OSC;
[0095] Figure 26 The pore area of 1.008 cm is summarized based on different HTL 2 Table of photovoltaic parameters of large-area OSCs;
[0096] Figure 27 shows the chemical structure of the active material of a pseudo-bilayer device according to some embodiments of the present invention;
[0097] Figure 28A JV curves of pseudo-bilayer OSCs based on different HTLs using D18 and 3-ClTh as active layers are shown.
[0098] Figure 28B is a table summarizing the photovoltaic parameters of pseudo-bilayer OSC devices based on different HTLs using D18 and 3-ClTh as active layers;
[0099] Figure 29 The IV curves of sandwich devices based on different HTLs (ITO / HTL / Ag) are shown;
[0100] Figure 30 shows the Mott-Schottky plots of devices including different HTLs at 100 kHz;
[0101] Figure 31 is a table summarizing the fitting parameters obtained from the Mott-Schottky plot;
[0102] Figure 32 The Nyquist plot obtained from the AC impedance spectrum is shown. The inset is the equivalent circuit used for data fitting.
[0103] Figure 33 is a table summarizing the fitting parameters from the Nyquist plot using equivalent circuit modeling;
[0104] Figure 34 shows a semi-logarithmic plot of the J-V plots of PM6-based devices at different HTLs measured in the dark;
[0105] Figure 35 The photocurrent density-effective voltage (J ph -V eff )picture;
[0106] Figure 36 It is a summary from the dark JV diagram and J ph -V eff Table of fitting parameters of characteristics. Determine R from dark JV plot s and R sh Around 1.5V and 0V respectively;
[0107] Figure 37 shows the MPP tracking of devices including different HTLs under continuous one-sun illumination;
[0108] Figure 38 The evolution of the normalized PCE for devices including different HTLs is shown. Parameters are the averages of four devices, where the errors are expressed as standard deviations.
[0109] Figure 39 The evolution of the normalized FF for devices including different HTLs is shown. Parameters are the average of four devices, where the error is expressed as the standard deviation.
[0110] Figure 40 shows the normalized V for devices including different HTLs OC The parameters are the average values of four devices, where the errors are expressed as standard deviations;
[0111] Figure 41 shows the normalized J of devices including different HTLs SC The parameters are the average values of four devices, where the errors are expressed as standard deviations;
[0112] Figure 42 The stability of pseudo-bilayer OSCs based on different HTLs using D18 and 3-ClTh as active layers after aging at 65 °C is shown.
[0113] Figure 43 shows the change in work function of HTL coated on ITO under accelerated thermal aging at 120 °C for 24 h;
[0114] Figure 44 shows the changes in the HOMO energy level of HTL coated on ITO under accelerated thermal aging at 120 °C for 24 h;
[0115] Figure 45 shows the AFM height image of fresh HTL film of single Br-PA under accelerated thermal aging at 120 °C for 24 h;
[0116] Figure 46 shows the AFM height image of fresh HTL film of HPWO under accelerated thermal aging at 120 °C for 24 h;
[0117] Figure 47 shows an AFM height image of a fresh HTL film of Br-PA:HPWO-SDC under accelerated thermal aging at 120°C for 24 hours; and
[0118] Figure 48 is a table summarizing the evaluation of product cost and processing complexity for different HTLs. DETAILED DESCRIPTION
[0119] As used herein, the forms "a", "an" and "the" are intended to include both the singular and the plural forms unless the context clearly indicates otherwise.
[0120] As used herein, the words "example" or "exemplary" are intended to serve as examples, instances, or illustrations. Any aspect or design described in this disclosure as "exemplary" is not necessarily to be construed as preferred or advantageous over other aspects or designs. Rather, the use of the words "example" or "exemplary" is intended to present concepts in a concrete manner. As used in this application, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or." That is, unless otherwise specified or the context dictates, "X employs A or B" is intended to mean any natural inclusive permutation. That is, if X employs A, X employs B, or X employs both A and B, then "X employs A or B" holds true in any of the foregoing cases.
[0121] As used herein, the word "about" is intended to refer to values that slightly deviate from the values recited herein.Examples have been described throughout this disclosure.
[0122] It is believed that the low conductivity of POM-based HTLs can be addressed by introducing dopants such as SnCl2 or SAM into the POM-based HTL. However, this may lead to problems such as energy level mismatch, especially under thick HTL conditions. In addition, the mixing strategy may cause problems, including the tendency of phase separation, enhanced parasitic absorption and sensitivity of device performance to the blending ratio. Although this can be circumvented by using an ultrathin POM layer of a few nanometers (under which conditions the charge is extracted by tunneling), this may in turn cause coverage problems on the anode substrate, where pinholes or nanovoids are inevitably formed. Such incomplete coverage of the HTL will gradually destroy the ohmic contact between the anode and the active layer under physical aging, thereby reducing the open circuit voltage (V) of the OSC due to the accumulation of charge carriers near the HTL caused by the energy mismatch. OC ) and fill factor (FF). Therefore, it is believed that complete coverage of a single layer or ultrathin HTL on the anode is crucial for the efficient and stable output of OSCs.
[0123] Without wishing to be bound by theory, the present inventors have devised a strategy through their own research, trials, and experiments that can achieve sufficient HTL coverage under thin-film conditions, thereby eliminating the need for thick-film HTL even when processed by rapid printing methods. The present inventors have devised that, through sequential deposition, POM can be integrated with SAM to form a tightly intercalated composite material. Specifically, the SAM can be enriched at the bottom, and the POM can act as both a void filler and a top surface passivator, resulting in improved surface profile and charge carrier density in OSC devices.
[0124] In a first aspect of the present invention, a composite material for an organic solar cell (OSC) is provided, the composite material comprising a self-assembled monolayer (SAM) of a polyoxometalate (POM) cluster and a carbazole-based compound. As used herein, the term "self-assembled monolayer" or "SAM" generally refers to a one-molecule-thick layer of material that is bound to a surface in an ordered manner due to physical or chemical forces during a deposition process. It should be understood that the molecules / compounds that form a one-molecule-thick layer may include the general structure of ALR, where A is a head group or anchor group that the molecule / compound adsorbs (such as by chemical adsorption) onto a substrate (such as a substrate of an organic solar cell); L is a tail group having a linker group at position 9, such as a carbazole tail group having a linker of ethyl, butyl, phenyl, etc.; and R is a functional group such as Cl, Br, methyl, methoxy, etc.
[0125] In particular, it is preferred that the compounds of the SAMs described herein are carbazole-based compounds. In some embodiments, the carbazole-based compounds may have the following formula:
[0126]
[0127] wherein: R1 and R2 each represent mono- or di-substitution and are each independently selected from the group consisting of hydrogen, halogen, alkyl, alkoxy, fused ring, non-fused ring, and combinations thereof; n is a positive integer from 1 to 3; and A is an anchor group comprising an acid moiety.
[0128] The alkyl group may be straight or branched and may have 1 to 6 carbon atoms. Examples of C1-C6 straight chain alkyl groups may include methyl, ethyl, propyl, butyl, pentyl, and hexyl. Examples of C1-10 branched chain alkyl groups may include isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl (pentyl), tert-pentyl, neopentyl, isopentyl (isopentyl / isoamyl), sec-pentyl, 3-pentyl, sec-isopentyl, activated pentyl, and the like.
[0129] As used herein, the term "alkoxy" generally refers to a functional group or substituent comprising an alkyl group singly bonded to an oxygen. Thus, the alkoxy groups described herein may be alkoxy groups derived from the aforementioned alkyl groups. Examples of such alkoxy groups may include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, tert-pentoxy, neopentoxy, isopentoxy, sec-pentoxy, 3-pentoxy, sec-isopentoxy, and the like.
[0130] Halogen generally refers to an element from Group 17 of the Periodic Table of Elements. Preferably, the halogen may be selected from the group consisting of F, Cl, Br, I, and combinations thereof.
[0131] The fused and non-fused rings may be aryl or heteroaryl. As described herein, the aryl group may have a total carbon number of 6 to 10. Examples of aryl groups may include phenyl, tolyl, tert-butylphenyl, xylyl, naphthyl, indenyl, azulenyl, cumyl, and the like. As described herein, the heteroaryl group may be a heteroaryl group derived from a heteroaryl compound having a total carbon number of 5 to 10. Examples of such heteroaryl compounds may include pyridine, indole, quinoline, isoquinoline, pyridazine, pyrimidine, benzofuran, benzo[c]thiophene, benzo[b]thiophene, isobenzofuran, quinoxaline, phthalazine, quinazoline, benzo[c][1,2,5]thiadiazole, benzo[d]isoxazole, and the like.
[0132] In some embodiments, R1 and R2 can each be independently selected from the group consisting of H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 alkoxy as described herein, C6-C10 aryl as described herein, C5-C10 heteroaryl as described herein, and combinations thereof.
[0133] In some embodiments, the anchoring group A can be selected from the group consisting of: carboxyl (-C(=O)OH), sulfonyl (-S(=O)2-OH), thiol (-SH) and phosphono (-P(=O)(-OH)2).
[0134] In various embodiments of the present invention, R1 and R2 may be the same or different. In some embodiments where R1 and R2 are the same, the carbazole-based compound may have a formula selected from the group consisting of:
[0135]
[0136] wherein: R1 and R2 each represent a monosubstitution and are selected from the group consisting of H, F, Cl, Br, I, methyl, ethyl, methoxy, ethoxy, tert-butoxy, and phenyl; n is 1-3; and A is selected from the group consisting of carboxyl, sulfo, mercapto, and phosphono.
[0137] In some specific embodiments, the carbazole-based compound having the same R1 and R2 may have a formula selected from the group consisting of:
[0138]
[0139]
[0140] wherein R1 and R2 are selected from the group consisting of Br, Cl, and phenyl; and n is 1 to 3. In some exemplary embodiments, the carbazole-based compound having the same R1 and R2 may have a formula selected from the group consisting of:
[0141]
[0142]
[0143] In some embodiments where R1 and R2 are different, the carbazole-based compound may have a formula selected from the group consisting of:
[0144]
[0145]
[0146] wherein: R1 represents a monosubstitution and is selected from the group consisting of H, F, Cl, Br, I, methyl, ethyl, methoxy, ethoxy, tert-butoxy, and phenyl; n is 1-3; and A is selected from the group consisting of carboxyl, sulfo, mercapto, and phosphono.
[0147] In some embodiments, the POM cluster may comprise a Keggin structure. Figure 1AThe Keggin structure may have a complete tetrahedral symmetry and may consist of one heteroatom Y surrounded by four oxygen atoms to form a tetrahedron. The heteroatom Y may be located at the center and caged by 12 octahedral MO6 and / or M'O6 units connected to each other by adjacent oxygen atoms. In some specific embodiments, the POM cluster having the Keggin structure may have the formula X a YM n M' 12-n O 40 , and wherein X can be a cation selected from the group consisting of: H + NH4 + NR4 + , wherein R is a C1-C4 linear or branched alkyl group as described herein; a is 3 or 4; Y is selected from the group consisting of Si and P; M and M' are selected from the group consisting of W and Mo; and n is 0-12.
[0148] In an exemplary embodiment, the POM cluster having a Keggin structure may have the formula H3PW 12 O 40 .
[0149] In some embodiments, the POM cluster may comprise a Dawson structure. Figure 1A and 1B , the Dawson structure can be considered as a fusion of two defective Keggin structures, in which three octahedra are missing. The Dawson structure can contain two oxygen anions Y at its core, one on each side of the elliptical anion. In some specific embodiments, a POM having a Dawson structure can have the formula X b Y2M n’ M' 18-n’ O 62 , and wherein X is a cation selected from the group consisting of: H + NH4 + NR4 + , wherein R is a C1-C4 linear or branched alkyl group as described herein; b is 6 or 8; Y is selected from the group consisting of Si and P; M and M' are selected from the group consisting of W and Mo; and n' is 0-18.
[0150] As mentioned above, advantageously, the POM clusters as described herein can serve as the gap fillers and surface passivators of SAM. In particular, the POM clusters can be configured to form a discontinuous layer on the SAM. Without wishing to be bound by theory, the inventors have devised that, by, for example, sequentially depositing the POM clusters onto the SAM, the POM clusters can be intercalated with the SAM by being filled into the nano-voids of the SAM, thereby forming a discontinuous passivator layer of the POM clusters on top of the SAM enriched at the bottom. It is also believed that when the composite material is used in the hole transport layer, this structural arrangement can be conducive to improving the efficiency and long-term stability of the organic solar cell. Therefore, in some embodiments, the composite material can be a hole transport layer material.
[0151] In some embodiments, the POM clusters and SAM may have a concentration ratio of about 1:1 to about 1:40, such as 1:0.9, 1:0.91, 1:0.92, 1:1, 1:1.01, 1:1.02, 1:39.6, 1:39.7, 1:39.9, 1:40.1, 1:40.2, 1:40.3, etc.
[0152] A method for preparing the composite material described herein will now be disclosed. The method may involve sequentially depositing a SAM and POM clusters on a substrate, such as a conductive substrate (e.g., ITO glass). In some embodiments, the method may include the following steps: a) depositing a SAM of a carbazole-based compound as described herein on a substrate to form a first substrate; and b) depositing POM clusters on the first substrate to form a discontinuous layer on the first substrate. In particular, steps a) and b) may each be performed by spin coating. For example, a SAM precursor solution containing a carbazole-based compound as described herein and a suitable solvent such as an alcohol (e.g., isopropyl alcohol, etc.) can be spin-coated on an ITO glass at a speed of, for example, about 2800 rpm to about 3200 rpm, about 2850 rpm to about 3200 rpm, about 2790 rpm to about 3200 rpm, about 2900 rpm to about 3150 rpm, about 2900 rpm to about 3010 rpm, about 2950 rpm to about 3000 rpm, etc., for about, for example, about 25 seconds to about 30 seconds to about 24 seconds to about 31 seconds, about 25 seconds to about 29 seconds, about 28 seconds to about 30 seconds, etc., to form a first substrate. Thereafter, the first substrate can be spin coated with a POM precursor solution containing POM clusters as described herein and a suitable solvent such as an alcohol (e.g., methanol, etc.) at a speed of, for example, about 3800 rpm to about 4200 rpm, about 3850 rpm to about 4200 rpm, about 3800 rpm to about 4250 rpm, about 3800 rpm to about 4100 rpm, about 3900 rpm to about 4050 rpm, about 3950 rpm to about 4000 rpm, etc., for a duration of, for example, about 25 seconds to about 30 seconds to about 24 seconds to about 31 seconds, about 25 seconds to about 29 seconds, about 28 seconds to about 30 seconds, etc.
[0153] Preferably, step b) of the method described herein is performed without pre-rinsing the first substrate. That is, after obtaining the first substrate, step b) is performed immediately to spin-coat the POM cluster precursor solution onto the first substrate. Without wishing to be bound by theory, it is believed that any excess carbazole-based compound not chemically adsorbed to the substrate in step a) will ultimately be removed by the solvent of the POM precursor solution in step b). Advantageously, this is believed to reduce the processing complexity of preparing the composite material described herein.
[0154] Without wishing to be bound by theory, it is believed that a dense layer of the composite material may be formed after step b). Therefore, in some preferred embodiments, step b) may be performed without post-annealing. In other words, after the spin coating in step b) is completed, it is not necessary to post-anneal the composite material formed. Advantageously, it is believed that this will further reduce the processing complexity of preparing the composite material described herein.
[0155] As mentioned above, the composite material as described herein is particularly suitable for use in organic solar cells, such as as a hole transport layer of an organic solar cell. Therefore, in a third aspect of the present invention, there is provided an organic solar cell comprising a hole transport layer, the hole transport layer comprising the composite material as described herein.
[0156] refer to Figure 1C , provides a cross-sectional view illustrating the structure of an organic solar cell (OSC) 100 according to an embodiment of the present invention. Figure 1C , the OSC in this embodiment includes an anode 102 , a hole transport layer (HTL) 104 , a photoactive layer 106 , an electron transport layer 108 and a cathode 110 .
[0157] Anode 102 can be made of any suitable material that can be used in an OSC. In some embodiments, the anode can be a metal sheet, such as a metal plate of Au, Cu, etc. In some other embodiments, the anode can include a substrate on which a conductive material is deposited. Examples of such anodes can include ITO glass, IZO glass, FTO glass, AZO glass, etc.
[0158] The HTL 104 can be disposed between the anode 102 and the photoactive layer 106, in particular, in direct contact with the anode and the photoactive layer. The HTL can be formed by depositing (in particular, spin coating, more particularly, sequentially depositing / spin coating) the SAM and POM clusters onto the anode using the preparation methods described herein. In some exemplary embodiments, the HTL 104 can be prepared by spin coating the SAM onto the anode, followed by thermal annealing and further spin coating with POM clusters to form an HTL having a dual-layer structure (i.e., a discontinuous layer of POM clusters on top of the SAM enriched at the bottom as described herein).
[0159] The photoactive layer 106 may be disposed between the HTL 104 and the ETL 108, and in particular, in direct contact with the HTL and the ETL. The photoactive layer may include at least one electron donor and at least one electron acceptor. Examples of electron donors may include, for example, Figure 1D One or more compounds shown in . Examples of electron acceptors may include Figure 1E One or more compounds shown in .
[0160] In some embodiments, the photoactive layer can be configured as one of the following structures: bulk heterojunction (BHJ), quasi-planar heterojunction (QPHJ), and pseudo-bilayer. The photoactive layer can be formed by one-step spin coating of a donor-acceptor blend solution, sequential spin coating of pure donor and acceptor solutions, etc.
[0161] The ETL 108 can be formed on the photoactive layer, such as by spin coating, and in particular, in direct contact with the photoactive layer. The ETL can be formed from a material having high electron transport capability. Examples of such materials include 2,9-bis(3-(bis(2-hydroxyethyl)amino)propyl)anthra[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetraone (PDINOH), poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] (PFN), and the like.
[0162] The cathode 110 is formed on the ETL 108, such as by vacuum deposition, and is particularly in direct contact with the ETL 108. Examples of suitable cathode materials may include Ag, Al, Zn, and the like.
[0163] As mentioned herein, the composite materials described herein are particularly suitable for use in organic solar cells and, when used in a hole transport layer, can improve the efficiency and long-term stability of organic solar cells. For example, as shown in Table 1 below, organic solar cells having a hole transport layer containing the composite materials described herein can produce a power conversion efficiency (PCE) of about 18.3% to about 19.4%.
[0164] Table 1 Energy conversion efficiency of OSC devices having a hole transport layer containing a composite material as described herein
[0165] Photoactive layer HTL PCE (%) PM6:BTP-eC9:L8-F Formula (IIA): HPWO 19.10 D18:3-ClTh Formula (IIB): HPWO 18.31 D18:L8-BO Formula (IIC): HPWO 19.40 D18:FQx-C9 Formula (IIIA): HPWO 18.64
[0166] *HPWO=Phosphotungstic acid hydrate
[0167] The detailed properties of the OSC described herein will be discussed in a later section of this disclosure.
[0168] Hereinafter, the present invention is described in more detail by way of examples, but the present invention is not limited thereto.
[0169] Example
[0170] Materials and methods
[0171] Material
[0172] The photoactive materials PM6 and BTP-eC9, as well as SAM and Br-PA, were purchased from Organtec Ltd. L8-F was purchased from HyperChemical Inc. PDINOH was synthesized according to a reported method. POM and HPWO (phosphotungstic acid hydrate) were purchased from Sigma-Aldrich and were reagent grade (purity ≥ 99.5%). HPWO was not dehydrated before use because removing the crystal water requires harsh annealing conditions at 300°C for 1 hour, and dehydration would inevitably lead to the formation of micropores in the solid electrolyte.
[0173] Solar cell manufacturing
[0174] The OSC device was fabricated using a pin structure of ITO / HTL / active layer / PDINOH / Ag. Pre-cleaned ITO (130 nm) glass was treated with oxygen plasma (50 W) for 30 minutes.
[0175] For single SAM HTL, Br-PA (0.5 mg mL -1 ) was spin-coated onto ITO at 3000 rpm in air for 30 seconds, followed by thermal annealing at 100° C. for 5 minutes. The cooled substrate was rinsed with isopropyl alcohol or methanol at 3000 rpm in air for 30 seconds, followed by thermal annealing at 100° C. for 5 minutes.
[0176] For single POM HTL, HPWO (0.5-5 mg mL -1 ) were spin-coated on ITO at 4000 rpm for 30 s in a nitrogen-filled glove box without any post-treatment.
[0177] For the SAM:POM composite HTL, Br-PA (0.5 mg mL -1 ) was spin-coated onto ITO at 3000 rpm in air for 30 s. After transfer into the glove box, the substrate was directly coated with HPWO (0.5 mg mL -1 ) were spin coated at 4000 rpm for 30 seconds without pre-rinsing with pure solvent or post-annealing.
[0178] The blend of PM6:BTP-eC9:L8-F (weight ratio: 1:0.9:0.3) was dissolved in chloroform with a donor concentration of 7.8 mg mL -1, and stirred at 50 °C for >1 hour. A small amount of diiodooctane (0.32 vol%) was added to the solution 10 minutes before deposition. The blended solution was spin-coated on the substrate at 3500 rpm for 35 seconds to obtain an active layer with a thickness of about 100 nm. The active layer was thermally annealed at 85 °C for 5 minutes. For pseudo-bilayer devices, D18 was dissolved in a concentration of 6 mg mL -1 3-ClTh (11 mg mL) in chloroform solution without solid additives was heated at 90 °C and then spin-coated onto a hot substrate at 3000 rpm for 30 s. -1 ) was coated thereon at 2800 rpm to form a pseudo bilayer with a thickness of about 110 nm. After thermal annealing at 80°C for 2 minutes, the substrate was rinsed with ethanol (50 μL) at 2800 rpm for 20 seconds. Then, a trifluoroethanol solution of PDINOH (1.5 mg mL -1 ) was coated thereon with a thin layer (about 10 nm) of PDINOH at 2800 rpm for 20 seconds. 1 Finally, through 4.14mm 2 The shadow mask is 5×10 -6 Silver (Ag) was deposited in a vacuum with a thickness of 100 nm.
[0179] For accuracy, a non-refractive mask was used during JV measurements to further limit the device active area to 3.30 mm. 2 For larger area devices, use a 2.5 x 2.5 cm 2 The device was fabricated on an ITO substrate. The active layer and transport layer were spin-coated onto the substrate under the same conditions as for the small-area case. The active area of the device was determined to be 1.09 cm by a shadow mask during silver deposition. 2 The aperture area is precisely 1.008cm 2 .
[0180] Instrumentation and characterization
[0181] Absorption and transmission spectra were recorded on a SHIMADZU UV-1700 spectrophotometer. Tapping mode atomic force microscopy (AFM) was performed on a Bruker MultiMode 8-HR AFM platform with an imaging Z-noise level of less than 30 pm. Energy dispersive X-ray spectroscopy (EDS) elemental mapping was performed on a high-resolution environmental scanning electron microscope (FEI / Philips XL30Esem-FEG) equipped with an EDS system using an accelerating voltage of 15 kV. Contact angle measurements were performed on a Dataphysics OCA40 Micro surface contact angle analyzer using deionized water and diiodomethane as wetting liquids.
[0182] The surface energy (γ) was evaluated according to the Owens-Wendt-Rabel-Kaelble (OWRK) method. d and γ p represents the surface energy from dispersion and polar forces, respectively. X-ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS) were performed on a ThermoFisher ESCALAB QXi X-ray photoelectron spectrometer. Non-monochromatic He I was used as the ultraviolet light source with an energy of 21.21 eV. The basic vacuum of the analysis chamber was approximately 2×10 -9 mbar, and the bias voltage applied during the test was 5V. Electron spin resonance (ESR) spectra were recorded on a Bruker A300 / E500 ESR spectrometer at 298K under nitrogen protection. Pure materials of Br-PA, HPWO, and PM6 were directly measured using powder samples. The Br-PA:HPWO sample was prepared by blending fine powders of the two materials in a 1:1 weight ratio. The PM6:HPWO (1:1) sample was obtained by first dissolving PM6 and HPWO in chloroform and methanol, respectively, then blending the solutions and thoroughly drying them under vacuum.
[0183] Mott-Schottky plots were measured at a fixed frequency of 100 kHz on an integrated platform from Paios (Fluxim AG). Electrochemical impedance spectroscopy (EIS) was measured on a CHI760E electrochemical workstation (NBeT group, Beijing). AC impedance measurements were performed in Z-θ mode with varying frequencies (100 to 100 kHz) and an AC drive bias of 5 mV. OC An equal constant DC bias is superimposed on the AC bias. The JV curves were measured using a computer-controlled Keithley 2400 source meter under a 1-sun, AM 1.5G solar simulator (Enlitech SS-F5). The light intensity was calibrated using a standard silicon reference cell certified by NREL and Fraunhofer to give a power of 100 mW cm -2 The EQE spectra were measured on an Enlitech QE-S system equipped with a standard silicon diode, with monochromatic light generated by a Newport 300W lamp. Dynamic MPP traces were recorded on an on-site stability measurement system (CRYSCO, Guangzhou) equipped with multiple sample chambers and automatic data acquisition components. The sample chamber was placed in a nitrogen-filled glove box, and the test device was not encapsulated during the measurement. A white LED lamp with adjustable light intensity was used as the light source, and an additional filter was loaded to cut off UV light.
[0184] The conductivity (σ) was measured according to Pouillet's law, σ = (I / V)(L / S), where V is the voltage, I is the current through the HTL film, L is the thickness of the HTL film, and S is the area of the device. The measurements were performed under dark conditions using a sandwich structure of ITO / HTL / Ag. All HTL films had a thickness of approximately 30 nm. PEDOT:PSS was deposited from its aqueous solution (Heraeus) at 3000 rpm. Br-PA was deposited from its isopropanol solution (10 mg mL -1 HPWO was prepared from its methanol solution (10 mg mL -1 ) was spin-coated at 4000 rpm. A Br-PA:HPWO mixture (2:1, weight ratio) was prepared from its isopropanol solution (10 mg mL -1 ) was spin coated at 3500 rpm.
[0185] Example 1
[0186] Preparation and properties of SDC-HTL
[0187] The deposition procedure of SDC-HTL consists of sequential coating of Br-PA and HPWO ( Figure 2 HPWO was chosen as the post-coating layer because its zero-dimensional nanostructure can fill the vacancies in the Br-PA base layer. The oxygen atoms surrounding the HPWO framework can be anchored to the ITO surface through the vacancies, thereby increasing surface coverage and suppressing the potential tail swing of the Br-PA under thermal stress.
[0188] Both Br-PA and HPWO were spin-coated from dilute alcohol solutions. Because the phosphonic acid groups of Br-PA are strongly anchored to the ITO substrate, HPWO can be coated onto it using non-orthogonal solvents without significantly damaging the underlying Br-PA layer. The Br-PA sublayer in the SDC-HTL is not rinsed with any solvent, as excess Br-PA molecules not chemisorbed by ITO can, in principle, be washed away by the alcoholic HPWO solution. Therefore, the SDC-HTL strategy does not increase processing complexity compared to the deposition of a single Br-PA HTL, which requires additional rinsing with pure solvent.
[0189] The transmittance of ITO substrates coated with different HTLs was measured by UV-visible spectroscopy with quartz as a reference ( Figure 3). All substrates showed similar high transmittances of >89% over the entire range of 400-1000 nm. However, in the NIR region (650-950 nm), ITO / Br-PA showed a slightly decreased transmittance (about 0.5%) relative to that of bare ITO, while the transmittance of ITO / HPWO did not change significantly compared to that of ITO. Interestingly, the transmittance of the Br-PA:HPWO composite was slightly higher than that of Br-PA alone. This should be the result of partial replacement of the chemically adsorbed Br-PA layer with HPWO during the SDC-HTL formation process (see Figure 2 ), indicating that the SDC-HTL strategy does not increase parasitic absorption when used in solar cells.
[0190] The thickness of the ultrathin SDC-HTL can be roughly estimated by combining step profiler measurements with extrapolation from the absorbance-thickness relationship (which assumes a linear dependence of absorbance on film thickness). The thickness of the ultrathin SDC-HTL can be roughly estimated by combining step profiler measurements with extrapolation from the absorbance-thickness relationship (which assumes a linear dependence of absorbance on film thickness). Figure 4 The results of different HPWO concentrations (from 0.5 to 8 mg mL -1 , and the concentration of Br-PA was fixed at 0.5 mg mL -1 By comparing the absorbance of the characteristic peak at 270 nm and measuring 8 mg mL -1 -Thickness of the film (about 20 nm), inferred 0.5 mg mL -1 -The film is about 3.4nm.
[0191] Figure 5A The UV photoelectron spectra (UPS) of different HTLs on ITO are shown. The Fermi level was determined by linearly extrapolating the high binding energy (BE) portion of the spectra. All HTLs resulted in a significant increase in WF (5.03-5.25 eV) compared to bare ITO (4.76 eV), confirming the great potential of these HTLs to form a better energy level alignment between the anode and the active layer ( Figure 5BSpecifically, Br-PA-coated ITO exhibited a higher WF (5.25 eV) than ITO coated with HPWO alone (5.03 eV), while the Br-PA:HPWO SDC exhibited a moderate WF of 5.20 eV. Further extraction of the UPS onset in the low BE region led to the calculation of the HOMO levels of ITO / Br-PA and ITO / Br-PA:HPWO, respectively, at -5.90 and -5.88 eV. The slightly upshifted HOMO level of the SDC-HTL could mitigate potential hole extraction blockage by the interfacial layer when fabricated as a thick film.
[0192] Example 2
[0193] Component distribution in SDC-HTL
[0194] The surface profiles of ITO substrates coated with different HTLs were investigated by atomic force microscopy (AFM). Br-PA-modified ITO showed a clear morphology with sharp contrast and a high root mean square roughness (RMS) of 3.39 nm, while ITO / HPWO showed a smaller feature size with a relatively low RMS of 3.05 nm. Figure 6A and 6B ). This means that HPWO monolayer can already be a good surface passivator for ITO. Br-PA:HPWO film shows a smoother surface and even lower RMS than pure HPWO ( Figure 6C ), which means that HPWO is not simply superimposed on top of Br-PA, but is mainly intercalated into the Br-PA layer, thus forming better coverage on the ITO. This also indicates that a better interfacial contact can be formed between the SDC-HTL and the active layer.
[0195] Energy dispersive X-ray spectroscopy (EDS) elemental mapping was performed on a high-resolution scanning electron microscope (SEM). The X-ray specific energy and Lα emission intensity of bromine (Br) and tungsten (W) were detected, and the 2.5×2.5μm X-ray maps of Br-PA and HPWO were mapped. 2 For both Br-PA and HPWO single-layer HTLs, the components are evenly distributed on the ITO ( Figure 7A and 7B However, the readily observed vacancies and pinholes in the monolayers (especially the HPWO films) confirm the incomplete coverage of these ultrathin HTLs on ITO. This is somewhat alleviated in SDC-HTLs, where Br-PA and HPWO are intercalated to form a dense film ( Figures 7C-7E ).
[0196] X-ray photoelectron spectroscopy (XPS) was further used to reveal the coverage and pattern of HTL on ITO. The P 2p and In 3d 3 / 2 The peaks of the ITO surface were fitted to determine the relative contents of Br-PA and / or HPWO molecules on the ITO surface. The fitted peak areas are summarized in Figure 8 In which according to P 2p:In 3d 3 / 2 The peak area ratio was used to obtain the P:In intensity ratio (see Figures 9A-9C In 3D 3 / 2 The single Br-PA shows a much higher P:In intensity ratio (0.018) than that of the single HPWO (0.003) ( Figure 10A and 10B ). In addition, the P:In intensity ratio of the Br-PA:HPWO composite material is 0.012 ( Figure 10C ), which is lower than the P:In intensity ratio of single Br-PA.
[0197] Considering that the composite material is obtained by sequential deposition, it should have two possible distribution patterns. One is a superposition pattern in which HPWO molecules are completely above the bottom Br-PA layer, and the other is an insertion pattern in which Br-PA molecules are enriched at the bottom and HPWO clusters fill in the vacancies of the bottom Br-PA layer while forming another discontinuous passivant layer on top. Based on the fact that the P:In ratio of the Br-PA:HPWO SDC layer is lower than that of the single Br-PA layer, it can be reasonably inferred that the composite material presents the following Figure 2 The latter model is depicted in .
[0198] To clarify whether HPWO in the composite material can be doped with Br-PA, the electron spin resonance (ESR) of pure powders of Br-PA and HPWO and their blends Br-PA:HPWO (1:1, weight ratio) were studied. Compared with the pure sample which showed only horizontal lines in the ESR spectrum ( Figure 11 ), a strong ESR signal with a g-factor of 2.003 (i.e., unpaired electrons) was observed for the Br-PA:HPWO blend, indicating that electron transfer may occur in the Br-PA:HPWO composite HTL.
[0199] Example 3
[0200] Interaction between SDC-HTL and active layer
[0201] The surface wettability of different HTLs was investigated by contact angle measurements. The water contact angle of the Br-PA monolayer was almost twice that of the HPWO film (90.1° vs. 48.6°). Figure 12A and 12BThe increased hydrophilicity of HPWO is basically detrimental to the long-term stability of OSCs because the water resistance will be reduced. However, the water contact angle exhibited by Br-PA:HPWO SDC (86.4°, Figure 12C ) is close to the water contact angle of single Br-PA, indicating much lower water wettability compared with single HPWO.
[0202] Combined with diiodomethane (CH2I2, Figures 13A-13C ) contact angles, and the surface energies (γ) of different HTLs were calculated using the Owens-Wendt-Rabel-Kaelble method, including dispersion (γ d ) and polarity (γ p ) component. It is worth noting that for HPWO films, the proportion of polar components is much higher, with the highest γ of 57.5 mN m among all HTLs. -1 ( Figure 14 ). Compared with single Br-PA, Br-PA:HPWO composites showed γ p Slightly increased, but at the same time γ d decreases, resulting in γ of 45.6 mN m -1 , slightly lower than the former 46.6mN m -1 This may be beneficial for enriching the polymer donor at the bottom surface of the active layer, which generally has a lower surface energy (lower than the surface energy of the non-fullerene acceptor).
[0203] It is believed that POM clusters have deep lowest occupied molecular orbital (LUMO) energy levels, which makes them easily reduced by additional electrons entering their metallic orbitals. Therefore, the possible p-doping between HPWO and the polymer donor PM6 was investigated by ESR. Figure 11 In the spectra shown in , a clear ESR response of the PM6:HPWO blend can be observed, while the ESR response of pure PM6 and HPWO powder is absent, confirming the occurrence of electron transfer from PM6 to HPWO.
[0204] This doping behavior was further verified by monitoring the oxidation state of the W 4f core levels via XPS. Figure 15A and 15B HPWO thin films (from 1 mg mL -1 The deconvolution of the W4f photoemission peak of ITO / HPWO produced two peaks with almost equal full width at half maximum (FWHM), among which W4f 5 / 2 The binding energy (BE) of W is centered at 38.5 eV, and W 4f 7 / 2 The binding energy is centered around 36.3 eV ( Figure 15CAs evaluated based on the positions and shapes of these peaks, they are considered to belong to the oxidized state W 6+ In the presence of PM6 (i.e., ITO / PM6 / HPWO), in addition to the two main peaks at 38.5 eV and 36.3 eV, a peak at 37.2 eV (W 4f 5 / 2 ) and 34.8eV(W 4f 7 / 2 ) become apparent. This clearly indicates the presence of W obtained by the reduction of HPWO by PM6. 5+ ions, confirming the p-doping between PM6 and HPWO.
[0205] Example 4
[0206] Performance of solar cells with different HTLs
[0207] Pin solar cells with an active layer of PM6:BTP-eC9:L8-F were fabricated to reveal the effect of HTL on device performance. The guest acceptor L8-F was included as a phase modifier with a weight ratio of 1:3 relative to the host acceptor BTP-eC9. The small molecule PDINOH ( Figure 16 ) was used as the electron transport layer (ETL) for all devices, considering that the possible anti-aggregation effect of the branched side chains could benefit the long-term stability of the devices.
[0208] For single HPWO devices, the range of 0.5 to 5 mg mL in methanol was screened. -1 The thickness of HPWO film was adjusted by the concentration of 0.5 mg mL -1 The solution-coated film produced the highest PCE of 17.1% ( Figure 17 ), namely V OC is 0.859V, short-circuit current density (J SC ) is 27.6 mA cm -2 , and the FF is 71.9%. Thicker HPWO leads to V OC and FF decreased sharply ( Figure 18A and 18B ), which may be due to the deep HOMO energy level (-7.75 eV) of HPWO which will hinder the hole extraction under thick film conditions (Figure 5).
[0209] The processing of Br-PA was carried out according to standard procedures. The device based on single Br-PA (rinsed with isopropyl alcohol) showed a higher PCE (17.7%) than that based on HPWO ( Figure 19A and 19B ), which is mainly due to their higher J SC (27.9mAcm -2) and FF (73.6%). Note that methanol rinsing of Br-PA leads to a PCE (17.6%) similar to that obtained from isopropanol rinsing, whereas the device including the as-cast SAM rinsed without solvent provides a much lower PCE (15.1%) ( Figure 20A and 20B ), confirming the importance of removing excess SAM molecules that are not chemically adsorbed by the substrate for OSC performance. Both Br-PA and HPWO devices were less efficient than the PEDOT:PSS-based control device, which provided 75.7% FF and 17.9% PCE, which may be attributed to the poor interface coverage in devices including monolayer or ultrathin HTL. However, the combination of Br-PA with HPWO (by 0.5 mg mL -1 The SDC-HTL integrated by methanol solution spin coating leads to a significantly increased PCE (19.1%) in the corresponding device, which is attributed to the improvement of all three parameters (V OC =0.869V, J SC =28.2 mA cm -2 , and FF = 77.5%).
[0210] Figure 21 The external quantum efficiency (EQE) of the Br-PA:HPWO device is shown to be slightly higher than that of the Br-PA counterpart in the 600-900 nm region, which is consistent with the slightly higher transmittance and smoother surface profile of the composite HTL. The HPWO device shows a lower EQE response than the other devices across almost the entire spectral region. This difference from the higher transmittance of HPWO can be attributed to the formation of major vacancies in the film that affect the interfacial ohmic contact. Compared with the integrated current density obtained from the current density-voltage (JV) characteristics, the integrated current density from the EQE ( Figure 22 ) within 4% mismatch.
[0211] With concentrations from even lower concentrations (0.1 mg mL in methanol) -1 )-coated HPWO SDC-HTL provided a similar PCE of 18.9% (i.e., V OC 0.871V, J SC 28.0 mA cm -2 , and FF is 77.4%))( Figure 23A and 23B ), which means that the changing HPWO concentration within the dilution ratio has a negligible effect on the Br-PA:HPWO ratio in the bottom layer of the SDC. Note that the one-pot processing of Br-PA:HPWO blend films leads to low PCE in OSCs regardless of the blending ratio ( Figure 24A and 24B), which may be due to the presence of excess Br-PA molecules that are not chemically adsorbed (which cannot be selectively removed by solvent washing because HPWO can also be washed away) and the uncertainty of the vertical pattern of the blend film. This indicates that the one-pot mixing of Br-PA and HPWO is not an effective way to integrate HTLs, and the composition ratio of the Br-PA:HPWO mixture is not a decisive factor for device performance.
[0212] Considering the fact that the optimal width of the subcells of solar modules is usually on the centimeter scale, the industrial potential of Br-PA:HPWO SDC was evaluated in centimeter-scale devices with a cell width of about 1 cm. Figure 25A As depicted, at 1cm 2 The tip efficiency of OSC is about 1-cm 2 A good PCE of 17.23% was achieved under the pore area ( Figure 25B and 25C ). As the device width increases, the J inevitably decreases. SC and FF are usually due to the formation of non-uniformity on the active layer and charge extraction attenuation caused by substrate resistance. However, compared with small area devices, 1-cm 2 The well-retained PCE in the device indicates the good compatibility of SAM:POM SDC with scale-up processing. 2 devices provided much lower PCEs of 15.91% and 15.51%, respectively. Figure 26 ), which means that the SAM / POM approach can also lead to significant enhancement of device performance in large-area devices, representing an important step towards industrially viable OSCs.
[0213] The effectiveness of SDC-HTL was further verified in a pseudo-bilayer blend system based on polymer donor D18 and non-fullerene acceptor 3-ClTh. Figure 27 ).according to Figure 28A and 28B From the photovoltaic performance shown in Figure 1, it can be noted that the PCE of 18.61% achieved in the Br-PA:HPWO device is higher than the PCEs of the PEDOT:PSS device and the Br-PA device (18.12% and 17.37%, respectively). This is due to the excellent V OC (0.868V) and J SC (27.91mA cm -2 ), which should be the result of the good interfacial contact and high visible-NIR transmittance of SDC-HTL. These results confirm that SAM:POM SDC can be a universal strategy for different material systems.
[0214] The conductivity (σ) of different HTLs was measured using a sandwich structure of ITO / HTL / Ag under dark conditions. Since ultrathin monolayers are not suitable for conductivity measurements, Br-PA was prepared as a bulk film with a thickness of approximately 30 nm. Therefore, a mixture of Br-PA:HPWO with a weight ratio of 2:1 was used as an alternative to SDC-HTL. Figure 29 The IV curves drawn in the figure show that the conductivity of PEDOT:PSS, Br-PA, HPWO and Br-PA:HPWO (2:1) are 1.38×10 -3 , 1.25×10 -3 , 1.68×10 -3 and 1.28×10 -3 S m -1 Notably, the conductivity of HPWO is higher than that of PEDOT:PSS, similar to what has been observed in previous reports. Br-PA exhibits lower conductivity than both PEDOT:PSS and HPWO, but this does not affect hole extraction since tunneling dominates in this monolayer HTL-based device. Br-PA:HPWO blends exhibit similar conductivity to pure Br-PA, indicating that the improved performance of Br-PA:HPWO devices is not due to changes in conductivity.
[0215] Capacitance-voltage (CV) measurements were performed to investigate the charge carrier concentration in PM6 devices including different HTLs. 2 -V relationship obtained from the Mott-Schottky characteristics ( Figure 30 ) to determine the doping density (N A ) and built-in voltage (V bi ). This is because the charge generated in the depletion region is entirely due to the dopant species. By adjusting the applied DC bias (V), the width of the depletion region will change, resulting in a charge that conforms to the formula 1 / C 2 =(2 / qε0ε r N A A 2 )(V bi -V), where q is the elementary charge, ε0 is the dielectric constant of vacuum, and ε r is the relative permittivity of the doped semiconductor, and A is the active area of the device. The parameters derived from the linear fit are summarized in Figure 31 HPWO device and Br-PA: HPWO device shows slightly higher N than Br-PA device A, which should be due to the p-doping of the polymer donor (PM6) by HPWO as demonstrated above. In addition, higher V was observed in the devices containing HPWO, especially the composite devices (0.838 V) compared with their counterparts carrying single Br-PA (0.824 V). bi This increase in V bi and the measured V OC The increase is well matched.
[0216] Figure 32 The Nyquist plots derived from the AC impedance spectra of PM6 devices including different HTLs measured in the dark are shown. Figure 32 The equivalent circuit model shown in the inset is fitted to the data, where the two capacitors represent the depletion capacitance (C 表面 ) and bulk capacitance (C 体 ). R 表面 and R 体 is with C 表面 and C 体 forms the resistance component of the parallel circuit, and R s represents the series resistance. The fitted capacitance and resistance values are summarized in Figure 33 R of SDC-HTL device 表面 301Ωcm based on Br-PA and HPWO 2 and 349Ωcm 2 Sharply dropped to 34Ωcm 2 This observation suggests that the charge carrier density in the composite interface increases, which is likely due to the combined effect of efficient p-doping and fewer surface vacancies at the interface. This observation suggests that the charge carrier density in the composite interface increases, which is likely due to the combined effect of efficient p-doping and fewer surface vacancies at the interface.
[0217] The dark JV curve and photocurrent density-effective voltage (J ph -V eff ) further confirms this point. For Br-PA device, HPWO device and Br-PA:HPWO device, the series resistance (R s ) were determined to be 0.80, 0.96, and 0.57 Ωcm 2 , and the shunt resistor (R sh ) were calculated to be 6.34×10 4 , 2.77×10 5 and 1.23×10 6 Ωcm 2 ( Figure 34 ). The lowest R of Br-PA:HPWO device s and the highest Rsh It is shown that including SDC-HTL can reduce ohmic losses in the device.
[0218] according to Figure 35 J shown in ph -V eff Curve, V eff >3V to determine saturation J ph (J ph,sat ), 28.05, 28.08, and 28.32 mA cm were obtained for Br-PA device, HPWO device, and Br-PA:HPWO device, respectively. -2 The value of ( Figure 36 ). J of SDC-HTL device ph,sat The higher the value, the greater the probability of exciton generation / dissociation in these devices. By determining the J near the MPP ph (J ph,MPP ) and J ph,sat ratio, evaluating the low V eff Region (V eff =0.2 V). The J values of Br-PA, HPWO, and Br-PA:HPWO devices were calculated. ph,MPP / J ph,sat The SDC-HTL devices show a higher charge collection probability than their pure Br-PA or HPWO-based counterparts, confirming the better interfacial contact achieved by the SDC-HTL strategy. These results also validate the higher J in solar cells including SDC-HTL. SC .
[0219] Example 5
[0220] Long-term thermal and light stability
[0221] To evaluate the long-term stability of solar cells containing different HTLs, unencapsulated PM6-based devices were aged in a nitrogen atmosphere under continuous heating at 65°C or tracked at the maximum power point (MPP) under continuous illumination from one sun. Thermal aging at 65°C was performed according to the "ISOS-D-2" test protocol of the International Organic Photovoltaics Stability Summit (ISOS). The aging temperature was considered to be higher than the maximum outdoor operating temperature. The light source for the MPP test was a white LED lamp with a simulated AM 1.5G spectrum and adjustable light intensity.
[0222] like Figure 37 and 38As shown in Figure 2, the Br-PA:HPWO SDC-HTL-based devices showed no aging characteristics under both thermal and MPP aging conditions. However, a gradual decrease in PCE was observed during the extended period of thermal aging, which was mainly due to the degradation of FF ( Figure 39 However, the PEDOT:PSS and Br-PA devices exhibited much higher original FF losses (approximately 11% FF loss), compared to the Br-PA:HPWO device, which showed only 6% loss of original FF after aging for approximately 1000 hours at 65°C. The HPWO device fared even worse, retaining only 82.4% of its original FF.
[0223] Another parameter that needs attention is V OC Br-PA:HPWO device provides a robust V OC , retaining 95.5% of the original value, while the VOC of PEDOT:PSS device, Br-PA device and HPWO device decreased to 88%-90% ( Figure 40 ).
[0224] Stable FF and V of Br-PA:HPWO devices OC This can be attributed to the robustness of the interfacial ohmic contact between the SDC-HTL and the active layer during thermal aging. SC are all stable ( Figure 41 ), so it has the most robust FF and V OC The SDC-HTL device showed the best stability, where the overall PCE was maintained at 88.0% ( Figure 38 This is much better than the overall PCE of their counterparts based on single Br-PA and single HPWO, which only retained 80.6% and 72.0% of the original PCE, respectively. The D18-based devices also showed excellent thermal stability when Br-PA:HPWO SDC was employed as the HTL. Compared to the PEDOT:PSS device, which retained 93.5% of the original PCE after aging at 65°C for about 400 hours, a higher value of 97.2% was maintained in the Br-PA:HPWO device, while showing no significant aging loss within the first 100 hours ( Figure 42 The MPP tracking curves of the PM6 device showed a similar decay trend to that observed in thermal aging. In contrast to the Br-PA device, which showed a rapid decrease in PCE within the first 20 hours, no obvious aging process was identified for the HPWO device and the Br-PA:HPWO device ( Figure 37However, the PCE of the HPWO device exhibited a sharp and sustained decrease after 200 hours, which could be related to the vacancies and pinholes observed in the HPWO layer. In contrast, the SDC-HTL device showed a slow decline throughout the aging period, retaining 92.5% of the original efficiency after a long MPP tracking period of 1030 hours.
[0225] In order to clarify the V OC UPS was used to track the changes in WF and HOMO energy levels, and AFM was used to monitor the changes in surface profile. To compare with fresh HTL, all HTL on ITO were subjected to accelerated thermal aging treatment at 120 °C in nitrogen atmosphere for 24 h. From the high BE part of the UPS spectrum ( Figure 43 ), a sharp decrease in WF was noted for aged Br-PA (from 5.25 to 5.02 eV) and HPWO (from 5.03 to 4.76 eV), while the WF of aged Br-PA:HPWO decreased much more slowly (from 5.20 to 5.12 eV). This largely explains the V OC The decrease of is much slower than that of Br-PA device or HPWO device.
[0226] By further extracting the UPS onset point in the low BE region, Br-PA exhibits a slightly upshifted HOMO energy level from -5.90 to -5.81 eV after aging, while the HOMO energy level of aged HPWO shifts significantly from -7.75 to -7.51 eV ( Figure 44 ). This means that aggregation may occur in the HPWO film during the aging process. For Br-PA:HPWO SDC, almost identical HOMO energy levels (-5.88 vs. -5.89 eV) were observed for fresh and aged films, indicating that the SDC strategy can effectively suppress the changes of each component under stress. To verify this, AFM of the aged HTL was further measured to reveal possible changes in the surface profile. Compared with the height image of the fresh HPWO film ( Figure 6B ), thermal aging leads to a significant increase in feature size and RMS in the aged HPWO film ( Figure 45 ). In contrast, for ITO / Br-PA ( Figure 6A and Figure 46 ) and ITO / Br-PA:HPWO( Figure 6C and Figure 47), no discernible changes in particle characteristics were observed, and surface roughness remained virtually unchanged or even decreased. This suggests that HPWO films tend to form aggregates during aging, while Br-PA and Br-PA:HPWO exhibit stable morphologies against thermal aging. HPWO's tendency to form aggregates is likely the root cause of the fastest degradation of HPWO devices under light and thermal stress.
[0227] As demonstrated above, in SDC-HTL, HPWO molecules primarily fill the vacancies of the SAM layer while forming another discontinuous layer on top. During aging, the bottom SAM-dominated layer will remain pinned by HPWO, while the upper discontinuous HPWO may undergo aggregation. Due to the formation of a dense SAM:HPWO layer at the bottom, possible changes in the ultrathin upper discontinuous HPWO do not significantly degrade the device performance. Therefore, SDC-HTL devices show better stability than either SAM devices or HPWO devices. These results confirm the superiority of integrating Br-PA with HPWO to modify the interfacial properties and improve the long-term stability of OSCs. Combined with the lower cost and easier processing of Br-PA:HPWO SDC relative to PEDOT:PSS ( Figure 48 ), it is believed that the SAM:POM SDC-HTL in this work will be an excellent candidate for replacing traditional HTL (such as PEDOT:PSS).
[0228] The present invention has been presented by way of example only, and various other modifications and / or alterations to the described embodiments may be made by those skilled in the art without departing from the scope of the invention as specified in the appended claims.
Claims
1. A composite material for an organic solar cell, comprising a polyoxometalate (POM) cluster and a self-assembled monolayer (SAM) of a carbazole-based compound.
2. The composite material of claim 1, wherein the carbazole-based compound has the formula: in: R1 and R2 each represent mono- or di-substitution and are each independently selected from the group consisting of hydrogen, halogen, alkyl, alkoxy, fused ring, non-fused ring, and combinations thereof; n is a positive integer from 1 to 3; and A is an anchoring group comprising an acid moiety.
3. The composite material of claim 2, wherein R1 and R2 are each independently selected from the group consisting of H, F, Cl, Br, I, C1-C6 alkyl, C1-C6 alkoxy, C6-C10 aryl, C5-C10 heteroaryl, and combinations thereof. The composite material of claim 2 , wherein A is selected from the group consisting of a carboxyl group, a sulfonyl group, a mercapto group, and a phosphono group. The composite material of claim 2 , wherein R1 and R2 are the same. The composite material of claim 2 , wherein R1 and R2 are different.
7. The composite material of claim 5, wherein the carbazole-based compound has a formula selected from the group consisting of: in: R1 and R2 each represent a monosubstitution and are selected from the group consisting of H, F, Cl, Br, I, methyl, ethyl, methoxy, ethoxy, tert-butoxy, and phenyl; n is 1-3; and A is selected from the group consisting of a carboxyl group, a sulfo group, a mercapto group, and a phosphono group.
8. The composite material of claim 6, wherein the carbazole-based compound has a formula selected from the group consisting of: in: R1 represents monosubstitution and is selected from the group consisting of H, F, Cl, Br, I, methyl, ethyl, methoxy, ethoxy, tert-butoxy and phenyl; n is 1-3; and A is selected from the group consisting of a carboxyl group, a sulfo group, a mercapto group, and a phosphono group.
9. The composite material of claim 7, wherein the carbazole-based compound has a formula selected from the group consisting of:
10. The composite material of claim 1, wherein the POM clusters comprise a Keggin structure.
11. The composite material of claim 1, wherein the POM clusters comprise a Dawson structure.
12. The composite material of claim 10, wherein the POM clusters have the formula X a YM n M' 12-n O 40 , and wherein X is a cation selected from the group consisting of: H + NH4 + NR4 + , wherein R is a C1-C4 linear or branched alkyl group; a is 3 or 4; Y is selected from the group consisting of Si and P; M and M' are selected from the group consisting of W and Mo; and n is 0-12.
13. The composite material of claim 12, wherein the POM clusters have the formula H3PW 12 O 40 .
14. The composite material of claim 11, wherein the POM clusters have the formula X b Y2M n’ M' 18-n’ O 62 , and wherein X is a cation selected from the group consisting of: H + NH4 + NR4 + , wherein R is a C1-C4 linear or branched alkyl group; b is 6 or 8; Y is selected from the group consisting of Si and P; M and M' are selected from the group consisting of W and Mo; and n' is 0-18.
15. The composite material of claim 1, wherein the POM clusters are configured to form a discontinuous layer on the SAM.
16. The composite material of claim 15, wherein the POM clusters are intercalated with the SAM by filling into the nanovoids of the SAM.
17. The composite material of claim 1, wherein the SAM and the POM clusters have a concentration ratio of 1:1 to 1:
40. The composite material according to claim 1 , which is a hole transport layer material.
19. A method for preparing the composite material according to claim 1, comprising the following steps: a) depositing a SAM of a carbazole-based compound on a substrate to form a first substrate; as well as b) depositing POM clusters on the first substrate to form a discontinuous layer on the first substrate.
20. The method of claim 19, wherein step b) is performed without pre-rinsing the first substrate.
21. The method of claim 19, wherein step b) is performed without post-annealing.
22. The method of claim 19, wherein step a) and step b) are each performed by spin coating. 23 . An organic solar cell comprising a hole transport layer, wherein the hole transport layer comprises the composite material according to claim 1 .
24. The organic solar cell according to claim 23, further comprising: an anode and a cathode, wherein the hole transport layer is disposed between the anode and the cathode; an electron transport layer, the electron transport layer being disposed between the anode and the cathode; as well as A photoactive layer is provided between the hole transport layer and the electron transport layer. 25 . The organic solar cell according to claim 24 , wherein the photoactive layer is in direct contact with the hole transport layer and the electron transport layer. 26 . The organic solar cell according to claim 24 , wherein the photoactive layer is configured as any one of the following structures: a bulk heterojunction, a quasi-planar heterojunction, and a pseudo-bilayer.